Study on the solid-state shear pulverization in shear flow conditions - Rusiecki, T.; Steller, R. (Polimery, 2022)
The results of PE-LD pulverization during either pressure or drag shear flows were presented. The processes have been carried out in specially designed heads with gap channels. The polymer was powdered in both flow alternatives' conditions. It was found that PE-LD pulverization occurred suddenly and in the whole mass of the polymer being in the field of suitably big shear forces. Temperature range observed, allowing this phenomenon occurring, was very narrow. Pulverization efficiency is the greatest at temperature about 104 oC and shear rate is in the range 0.1-10 s-1. Contrary to the past literature contributions it was stated that high pressure is not a necessary condition of pulverization as this phenomenon occurred also during drag flow with no pressure. Sieve analysis was used for characterization of grain size distribution and average size of grain of the products formed in various conditions of the process in pressure alternative (Table 1, Fig. 6a, b).